The relationship between technological changes and computer anxiety among employees in banking sectors / Maimunah Mohd Shah - Mohd Shah, Maimunah (Institute of Graduate Studies, UiTM, 2013)
The growing role of computers and technology in the workplace has changed the office landscape dramatically and necessitated employees to be competent and knowledgeable in order to manage computers effectively. Nevertheless, this adaptation to technology creates anxiety prompting much research in the area particularly focusing on schools, universities and younger or elderly adults. Research into computer anxiety experienced in commercial organisations has been much neglected. This study fills this gap by examining and determining the level of computer anxiety, attitude towards computers and technology acceptance among employees in commercial banks. Survey data gathered from 377 employees in various commercial banks in Kuala Lumpur was used to compare relationships between the stated variables and to assess if demographic characteristics like gender and job category played a moderating role in such relationships…